2022
DOI: 10.1080/21655979.2022.2052652
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells inhibited the apoptosis of alveolar epithelial cells caused by ARDS through CXCL12/CXCR4 axis

Abstract: Mesenchymal stem cells (MSCs) have a wide range of anti-inflammatory and immunomodulatory effects and have been observed to have potential therapeutic potential in the clinical treatment of various diseases. We pretreated lung cancer cells A549 with tumor necrosis factor (TNF-α), knocked down the key chemokine receptor CXCR4 on MSCs using lentivirus, and induced acute respiratory distress syndrome (ARDS) mouse model using lipopolysaccharide (LPS) and CXCL12 expression in vivo by adeno-associated virus (AAV-rh1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…SDF-1 is a pivotal chemokine that plays essential roles in the maintenance, mobilization, and attraction of stem cells, with its expression notably upregulated at injury sites to draw MSCs, which express the CXCR4 receptor, to the damaged regions [38,39]. Our findings demonstrated that PDF induced an increase in SDF-1 expression in rat peritoneum, peritoneal cavity, peripheral blood, and PMCs.…”
Section: Discussionmentioning
confidence: 62%
“…SDF-1 is a pivotal chemokine that plays essential roles in the maintenance, mobilization, and attraction of stem cells, with its expression notably upregulated at injury sites to draw MSCs, which express the CXCR4 receptor, to the damaged regions [38,39]. Our findings demonstrated that PDF induced an increase in SDF-1 expression in rat peritoneum, peritoneal cavity, peripheral blood, and PMCs.…”
Section: Discussionmentioning
confidence: 62%
“…When CXCR4/CXCL12 axis was knocked out, the inhibitory effect of MSCs on lung injury disappeared. These findings proved that the CXCR4/CXCL12 axis mediated the repair effect of MSCs on lung tissue injury 105 …”
Section: Cxcr4/cxcl12 Axis–mediated Inflammatory Diseasesmentioning
confidence: 52%
“…These findings proved that the CXCR4/CXCL12 axis mediated the repair effect of MSCs on lung tissue injury. 105 AMD3100 is the most commonly used CXCR4 antagonist in the studies on asthma. A natural serum albumin fragment, EPI-X4, is also a potential peptide anti-CXCR4 drug, which can bind to CXCR4 with high affinity and inhibit its activity.…”
Section: Cxcl12/cxcr4 Axis In Inflammatory Airway Diseasementioning
confidence: 99%
“…After dewaxing and rehydrating with xylene and ethanol of different concentrations, the sections were processed by the following steps: staining with hematoxylin (G1120, Solarbio, China) solution for 30 s, rinsing with running water for 5 min, soaking in 1% acid alcohol for 5 s, and counterstaining with eosin Ysolution (G1120, Solarbio, China) for 2 min. Smith pathological score system was used for evaluating pathological injury of lung tissue (He et al, 2022).…”
Section: Methodsmentioning
confidence: 99%